2021
DOI: 10.47525/ulasbid.879094
|View full text |Cite
|
Sign up to set email alerts
|

Hemşi̇releri̇n Kanita Dayali Hemşi̇reli̇k Uygulamalarina Yöneli̇k Tutumlarinin İncelenmesi̇

Abstract: Günümüzde tüm alanlarda olduğu gibi sağlık alanında da bilgiler hızla yenilenmekte ve gelişmektedir. Bu durum sağlık alanında gelenekselden ziyade kanıta dayalı uygulamalara doğru eğilimi arttırmaktadır. Bu araştırmanın amacı; hemşirelerin kanıta dayalı hemşireliğe yönelik tutumlarını değerlendirmektir. Yöntem: Tanımlayıcı ve kesitsel tipteki bu çalışma, Ekim 2018-Ocak 2019 tarihleri arasında bir devlet hastanesinde çalışan 63 hemşire ile yapılmıştır. Araştırmanın verileri "Hemşire Tanıtım Formu" ve "Kanıta Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In a different study in the literature, it was reported that nurses' attitudes towards EBN practices were negative (27). Considering both our study and other recent studies, the studies concluded in recent years show that the attitude towards EBN has increased positively (13,18,(20)(21)(22)(23)(24)(25) (32,33). It was observed that the findings of the studies on PSC examined in the literature were similar to the findings of this study (14,(29)(30)(31)(32)(33) In the studies in the literature where PSC is analysed, it can be said that the mean PSC scores are higher among nurses working in surgical units (29,30).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In a different study in the literature, it was reported that nurses' attitudes towards EBN practices were negative (27). Considering both our study and other recent studies, the studies concluded in recent years show that the attitude towards EBN has increased positively (13,18,(20)(21)(22)(23)(24)(25) (32,33). It was observed that the findings of the studies on PSC examined in the literature were similar to the findings of this study (14,(29)(30)(31)(32)(33) In the studies in the literature where PSC is analysed, it can be said that the mean PSC scores are higher among nurses working in surgical units (29,30).…”
Section: Discussionsupporting
confidence: 73%
“…This study concluded that the attitudes of nurses working in surgical clinics towards EBN were at a high level with a score of 60.07±6.01 ( (13,18,(20)(21)(22)(23)(24)(25). The attitudes towards EBN examined in the literature were found to be similar to the findings of our study (13,18,(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation